2017
DOI: 10.2215/cjn.00970116
|View full text |Cite
|
Sign up to set email alerts
|

Mean Corpuscular Volume and Mortality in Patients with CKD

Abstract: In patients with stages 3-5 CKD, mean corpuscular volume was associated with all-cause mortality, cardiovascular disease mortality, and infection-associated mortality, independent of other factors. The underlying pathophysiologic mechanisms warrant additional investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 28 publications
(32 reference statements)
4
41
1
3
Order By: Relevance
“…Increasing such variables of the red component of blood cells decreases the sperm quantity and quality, although a clear cause‐effect relationship could not be established. This is in line with previous studies detecting an impairment in human health status when erythrocyte distribution 31‐35 and the average globular volume increase, 36‐38 suggesting that sperm parameters are potential health markers 7 …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Increasing such variables of the red component of blood cells decreases the sperm quantity and quality, although a clear cause‐effect relationship could not be established. This is in line with previous studies detecting an impairment in human health status when erythrocyte distribution 31‐35 and the average globular volume increase, 36‐38 suggesting that sperm parameters are potential health markers 7 …”
Section: Discussionsupporting
confidence: 92%
“…Two parameters of impaired human health, erythrocyte distribution 31‐35 and average globular volume, 36‐38 were inversely related to total sperm number (adjusted R‐squared: 0.002; coefficient: −4.109 and −0.582, P < .010 and P < .050, respectively) and concentration (adjusted R ‐squared: 0.004; coefficient: −17.022 and −2.229, P < .001 and P < .001, respectively). Moreover, these two blood parameters were inversely related to total sperm motility (adjusted R ‐squared: 0.008; coefficient: −2.658 and −0.237, respectively; P < .001), and directly related to immobility sperm rate (adjusted R ‐squared: 0.008; coefficient: 2.653 and 0.237, P < .010 and P < .050, respectively).…”
Section: Resultsmentioning
confidence: 98%
“…Elevated MCV (generally > 100 fL) is often characteristic of underlying conditions such as nutritional deficiencies, drug and alcohol use [7], vitamin B12 deficiency [8], certain medications or bone marrow disorders [9]. In patients with ≥ 3 chronic kidney disease (CKD) stages, MCV was associated with all-cause mortality, cardiovascular disease mortality, and infectionassociated mortality [10]. Other authors [11] applied Cox regression analysis MCV to predict composite cardiovascular (CV) events in CKD patient as a major confounding factor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Braekkan et al 11 that hematocrit was an independent risk factor for hypertension in the general population. In addition, previous studies have shown that high mean corpuscular volume (MCV) is a prognostic indicator for acute decompensated heart failure 13 and that it is associated with all-cause mortality, cardiovascular disease mortality, and infectionassociated mortality in patients with chronic kidney disease stages 3-5, 14 and that mean corpuscular hemoglobin (MCH) is a predictor of iron deficiency. 15 Although numerous studies have indicated that lifestyle factors such as smoking, alcohol consumption, shift work, and exercise may exert an important effect on WBC count, [16][17][18][19] little is known about the association between hematological parameters and lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%